Acute effects of 3G mobile phone radiations on frontal haemodynamics during a cognitive task in teenagers and possible protective value of Om chanting. (3rd May 2016) - Bhargav, Hemant; N. K., Manjunath; Varambally, Shivarama; Mooventhan, A.; Bista, Suman; Singh, Deepeshwar; Chhabra, Harleen; Venkatasubramanian, Ganesan; T. M., Srinivasan; H. R., Nagendra
Abstract: Mobile phone induced electromagnetic field (MPEMF) as well as chanting of Vedic mantra 'OM' has been shown to affect cognition and brain haemodynamics, but findings are still inconclusive. Twenty right-handed healthy teenagers (eight males and 12 females) in the age range of 18.25 ± 0.44 years were randomly divided into four groups: (1) MPONOM (mobile phone 'ON' followed by 'OM' chanting); (2) MPOFOM (mobile phone 'OFF' followed by 'OM' chanting); (3) MPONSS (mobile phone 'ON' followed by 'SS' chanting); and (4) MPOFSS (mobile phone 'OFF' followed by 'SS' chanting). Brain haemodynamics during Stroop task were recorded using a 64-channel fNIRS device at three points of time: (1) baseline, (2) after 30 min of MPON/OF exposure, and (3) after 5 min of OM/SS chanting. RM-ANOVA was applied to perform within- and between-group comparisons, respectively. Between-group analysis revealed that total scores on incongruent Stroop task were significantly better after OM as compared to SS chanting (MPOFOM vs MPOFSS), pre-frontal activation was significantly lesser after OM as compared to SS chanting in channel 13. There was no significant difference between MPON and MPOF conditions for Stroop performance, as well as brain haemodynamics. These findings need confirmation through a larger trial in future.